Identifikasi Tebal Plat Lambung Kapal Tanker Tyche IMO 8794891 Dengan Ultrasonic Thicness Gauge - Aulia Fajrin; Mutiarani Mutiarani; Nugroho Pratomo Ariyanto; Wissesa Wissesa (Jurnal Teknologi dan Riset Terapan (JATRA), 2022)
NDT means testing without damaging the material or specimen. One of the NDT equipment that can be used to measure the thickness of the hull plate is the Ultrasonic Thickness Gauge (UTG). This tool uses sound waves that are reflected and received by the probe and converted to numerical data, the number is used to see the thickness of the plate material. The research purpose is identifying the thickness of tanker Tyche hull plate by Ultrasonic Thickness Gauge (UTG). Based on data from the Tyche hull shell opening table on the portside and sideboard the smallest test results are 9.7 mm. These results are still included in the tolerance because if the initial plate thickness is calculated from 12 mm – 2.4 mm, then the minimum acceptable thickness is 9.6 mm. If it is found that the plate thickness is below 9.6 mm based on the standards from the Indonesian Classification Bureau (BKI), the plate will be declared NG (Not Good) and the replating process will be carried out. Based on the test table, no UTG results were found which were below the standard plate thickness that had been set. Therefore, the Tyche tanker with the IMO code 8794891 is still feasible to operating and there is no need for a partial or complete replating process.